Are there any true marine Chlorella species? Molecular phylogenetic assessment and ecology of marine Chlorella-like organisms, including a description of Droopiella gen. nov. Issue 8 (17th November 2019) - Darienko, Tatyana; Rad-Menéndez, Cecilia; Campbell, Christine; Pröschold, Thomas
Abstract : Green algal species of spherical cell shape are generally considered to belong to the genus Chlorella, which are mostly freshwater or terrestrial organisms. Phylogenetic studies have shown that this genus is polyphyletic and belongs to different classes. However, until now, only freshwater or terrestrial strains have been studied. Here we investigated 11 strains of 'marine' Chlorella deposited in public culture collections, which we studied using an integrative approach. These strains were largely isolated from marine rock pools and brackish estuaries. SSU and ITS regions of the nuclear encoded ribosomal DNA were sequenced, ribosomal secondary structures were analysed and cell morphology, salinity tolerance and reproduction were examined. Our results showed that the marine strains are also of polyphyletic origin. Surprisingly, three marine isolates belong to Chlorella vulgaris according to the phylogenetic analyses, but showed a high phenotypic plasticity. Whereas these strains showed the typical morphology of C. vulgaris under freshwater conditions, they increased the cell shape and formed cell packages under marine conditions. In contrast, the other investigated strains showed no changes after changing the media. Two of the investigated strains belong to the genus Chloroidium, and those remaining represent a new genus, Droopiella .